Amenability of Euthynnus affinis to Preparation of Masmin - like Products by a Modified Process - P., Ravindranathan Nair; T.S., Unnikrishnan Nair; K., George Joseph; Mathen, Cyriac (Fishery Technology, 2025)
Euthynnus afinis has been processed to products resembling masmin and masmin lakes by cooking the dressed and brined fish under steam pressure followed by cooling, separation of the fillets (shredding for lakes) and alternate drying and smoking. The process yielded 4% more product than the traditional method. Preparation of masmin lakes can be achieved in 3 days compared to 10 days for masmin production. Both masmin and masmin flakes from E. afinis were graded very good and palatable. The water soluble protein and non - protein nitrogen were higher in the product prepared by the modified process.